Business Process as the Basis of the Process Approach in Enterprise Management - Nagym Ainel Nurlankyzy (International Journal of Engineering and Management Research, 2019)
The quality of enterprise management can be increased through the usage of balanced system of process approach. Business processes are inherent to any organization. Management accounting for each business process allows to conduct factor analysis when minimize labour costs and assess the their contribution to the implementation of the overall strategy. This article introduces the research of Business process used in enterprise management, delineates how to separate processes into groups, describes their characteristics, and differences between them.